Intelligent systems for healthcare management and delivery - Bouchemal, Nardjes, 1977- (Advances in healthcare information systems and administration (AHISA) book series., 2019)
"This book explores relevant and advanced methodological, technological and scientific approaches related to the application of sophisticated exploitation of artificial intelligence in intelligent systems for healthcare management and delivery. It also provides an insight of the technologies and intelligent applications that have received growing attention in recent years from various perspectives"--Provided by publisher